2010
DOI: 10.1099/ijs.0.012088-0
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus sequence analysis of root nodule isolates from Lotus arabicus (Senegal), Lotus creticus, Argyrolobium uniflorum and Medicago sativa (Tunisia) and description of Ensifer numidicus sp. nov. and Ensifer garamanticus sp. nov.

Abstract: Nine isolates from Argyrolobium uniflorum, Lotus creticus, Medicago sativa (Tunisia) and Lotus arabicus (Senegal) were analysed by multilocus sequence analysis (MLSA) of five housekeeping genes (recA, atpD, glnA, gltA and thrC), the 16S rRNA gene and the nodulation gene nodA. Analysis of the individual and concatenated gene sequences demonstrated that the nine new strains constituted three stable, well-supported (bootstrap and gene sequence similarity values) monophyletic clusters, A, B and C, all belonging to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 54 publications
0
33
1
Order By: Relevance
“…To end the debate, the Judicial Commission of the International Committee on Systematics of Prokaryotes made a final decision that Ensifer takes priority over Sinorhizobium and should be used at least in official journals, such as the International Journal of Systematic and Evolutionary Microbiology (Young, 2010). Since then, the names of eight novel species and new combinations have been validly published within the genus Ensifer, including Ensifer garamanticus (Merabet et al, 2010), Ensifer numidicus (Merabet et al, 2010), Ensifer mexicanus (Lloret et al, 2007), Ensifer sojae (Li et al, 2011a), Ensifer americanus (Wang et al, 2013), Ensifer psoraleae (Wang et al, 2013), Ensifer sesbaniae (Wang et al, 2013) and Ensifer morelensis (Wang et al, 2013).…”
mentioning
confidence: 99%
“…To end the debate, the Judicial Commission of the International Committee on Systematics of Prokaryotes made a final decision that Ensifer takes priority over Sinorhizobium and should be used at least in official journals, such as the International Journal of Systematic and Evolutionary Microbiology (Young, 2010). Since then, the names of eight novel species and new combinations have been validly published within the genus Ensifer, including Ensifer garamanticus (Merabet et al, 2010), Ensifer numidicus (Merabet et al, 2010), Ensifer mexicanus (Lloret et al, 2007), Ensifer sojae (Li et al, 2011a), Ensifer americanus (Wang et al, 2013), Ensifer psoraleae (Wang et al, 2013), Ensifer sesbaniae (Wang et al, 2013) and Ensifer morelensis (Wang et al, 2013).…”
mentioning
confidence: 99%
“…Ensifer kummerowiae, Ensifer medicae, Ensifer meliloti, Ensifer mexicanus, Ensifer morelense, Ensifer numidicus, Ensifer psoraleae, Ensifer saheli, Ensifer sesbaniae, Ensifer sojae and Ensifer terangae (Casida Jr, 1982;Li et al, 2011;Lloret et al, 2007;Martens et al, 2008;Merabet et al, 2010;Wang et al, 2013;Yan et al, 2016;Young, 2003). In order to clarify the accurate taxonomic position of this novel Ensifer group, we performed the present study to compare it with the defined Ensifer species.…”
mentioning
confidence: 99%
“…A year later, Zeigler (2003) found that a smaller number of genes, or even a single, carefully selected core gene, can equal or even surpass the precision of DNA-DNA reassociation for the quantification of genome relatedness and assigning related bacteria to the correct species. The taxonomic potential of the MLSA technique, confirmed by DNA-DNA relatedness, has allowed the assignment of many nodule bacteria into species (Martens et al, 2008;Merabet et al, 2010;Rincó n-Rosales et al, 2009;Vinuesa et al, 2005). The MLSA technique has also been applied for rapid and reliable species identification in other bacterial genera, e.g.…”
Section: Resultsmentioning
confidence: 99%